Twitter’s Fake News Discourses Around Climate Change and Global Warming - Al-Rawi, Ahmed; OʼKeefe, Derrick; Kane, Oumar; Bizimana, Aimé-Jules (Frontiers in Communication, 2021)
In this empirical study, we collected about 6.8 million tweets that mentioned “fake news”, and we extracted references to climate change and/or global warming to understand the public discourses around these two issues. Using a mixed method, the study’s findings show that there is a clear politically polarized discussion on climate change. We found that the majority of tweets focus on the U.S. context though references to other Western coutnries are often made. The anti-Liberal or anti-Democratic online community was more active on Twitter than the anti-conservative or anti-Republican community. Also, more than half the examined most retweeted posts contained claims about climate change being a natural cycle or even denying it exists, while about a third of these tweets stated that climate change was anthropogenic. The implications of the study are discussed, we argue that fake news as a term has a hollow meaning as it is used as a buzzword to discredit opponents and further the political agenda of different parties not only in the USA but also in other Western countries like Australia.